Police ethics and police community relations - Florendo, Adelene M. (Quezon City: Wiseman's Books Trading, Inc., 2008)
Cover title: Revised police ethics and police community relations
Includes bibliographical references and glossary.
Keywords: Police -- Ethics; Police -- Comunity relations